Polymers: 5D Entanglement in Star Polymer Dynamics (Adv. Theory Simul. 11/2018). Issue 11 (6th November 2018) - Korolkovas, Airidas
Abstract : A cross‐section view into a web of interpenetrated polymer chains is shown. Above the glass transition temperature, the molecules are able to diffuse. In article number1800078, Airidas Korolkovas demonstrates that, for long star‐shaped polymers, the mean square displacement is proportional to a power law 1/16 of time. This particular number is a signature of topological entanglement in exactly 5 dimensions.